Predicting coefficient of volume compressibility of fine-grained soils using appropriate soil type and soil state parameters - K. S. Vivekananda; H. B. Nagaraj (Scientific Reports)
Abstract Predicting the coefficient of volume compressibility (m v ) would help a field engineer to make a quick estimate of the soil compressibility. The multiple correlations suggested by various researchers as available in the literature indicate the importance of predicting the m v of soil. The existing correlations as available in literature either use soil state (in the form of SPT N-value or unconfined compressive strength or natural water content) or soil type (in the form of plasticity properties). However, using both soil type and soil state parameters in developing any prediction equation would be more reliable. To overcome this limitation of existing correlation equations to predict m v , a simple and reliable method that can be universally applied with appropriate soil type parameter represented by the Shrinkage Index (Liquid Limit-Shrinkage Limit) and soil state parameter represented by standardized SPT N 60 has been proposed. This model is designed to be universally applicable, serving as a valuable tool for practicing engineers and researchers to predict m v .